Screening of Antenatal Mothers and Prevention of Perinatal Group B Streptococcal Infection - Raj, M.; Razali , N.; Sulaiman, S. (2009)
The objectives of this study were: (1) to detect group B streptococcus (GBS) carriers among antenatal patients during pregnancy ( 35 to 37 weeks) in the University Malaya Medical Centre (UMMC), Kuala Lumpur, Malaysia, and (2) to give antibiotic prophylaxis during the intrapartum period for the GBS carrier patients. The aim is to prevent early onset of GBS infection in newborn. This pilot study was carried out from 1st July 2005 to 31st August 2005. It is a prospective study involving 56 pregnant women who were seen at the antenatal clinic in the UMMC between 35 to 37 weeks gestation. High vaginal swab and low vaginal together with endoanal swab were taken for culture and sensitivity. The antibiotic prophylaxis was started early in the intrapartum period for patients with positive culture for GBS. GBS was detected in 18 patients which contributes to about 32% of the study population. The proper choice of antibiotic is important in successful disease prevention.